2018
DOI: 10.1016/j.enconman.2017.12.097
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a premixed combustion large marine two-stroke dual fuel engine for optimising engine settings via parametric runs

Abstract: As the environmental regulations have become more stringent, the shipping industry has been focusing on more efficient and environmentally friendly means of propulsion and electric power generation. In this respect, dual fuel engines, which operate either in diesel mode or dual fuel (DF) mode by burning diesel fuel or natural gas and pilot diesel fuel to initiate ignition respectively, has become one of the most promising solutions as their dual fuel operation leads to reduced nitrogen oxide (NOx), carbon diox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…As reported in [17,18], very few studies have been published focusing on the modelling/simulation or experimental analysis of marine DF engines. The more recent authors' studies [19,20] presented the transient simulation of a large marine DF engine and the derived results were employed for the safety analysis of the engine operations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in [17,18], very few studies have been published focusing on the modelling/simulation or experimental analysis of marine DF engines. The more recent authors' studies [19,20] presented the transient simulation of a large marine DF engine and the derived results were employed for the safety analysis of the engine operations.…”
Section: Introductionmentioning
confidence: 99%
“…Theotokatos et al [20] reported the extension of the model presented in [18] and simulated critical situations of the engine operation considering normal and delayed exhaust gas waste gate valve control providing recommendations for enhancing the engine safety. In Mavrelos and Theotokatos [17], a large marine DF two-stroke engine of the premixed combustion type was investigated based on a steady state 0D model developed in the GT-ISE software and the parametric optimisation of the engine settings was performed with the aim of simultaneously reducing the CO 2 and NOx emissions. In Ritzke et al [27], a combined 0D/1D and computational fluid dynamics (CFD) three-dimensional (3D) approach was proposed for modelling a four-stroke dual fuel marine engine in the AVL Boost and FIRE software tools.…”
Section: Introductionmentioning
confidence: 99%
“…Gas engines have been increasingly employed as prime movers in transport vehicles [1] and electricity generators [2]. Natural gas (NG) is typically used as the primary fuel for gas engines [3], whilst biogas and pyrolysis gas are also used in countries with abundant biomass or energetic waste resources [4].…”
Section: Introductionmentioning
confidence: 99%
“…Half-way between the 0D and 3D approach, there is the quasi-dimensional (QD approach. It does not have the spatial resolution of 3D simulations, but divides the combustion site into logical zones like fuel, fresh air, and combustion products, as shown by Mavrelos et al [17] for a large marine two-stroke, dual fuel engine. QD models allow some insight into the formation of pollutants, but lack the dimensionality of 3D simulations.…”
mentioning
confidence: 99%